Artificial Intelligence and Professional Boundaries in Journalism: Resistance, Adaptation, and Implications for Professional Education - Çipuri, Ramadan; Luarasi, Iris (European Journal of Social Science Education and Research, 2026)
This study analyses the impact of Artificial Intelligence (AI) on the construction of professional boundaries within Albanian media newsrooms. The analysis is grounded in the theoretical concept of boundary work (Carlson & Lewis, 2015), which conceptualises journalism as a field in continuous negotiation shaped by the interaction between professionals and external actors. The study combines quantitative and qualitative approaches. The quantitative data were obtained through a survey of 236 journalists, conducted as part of a study by the Department of Journalism and Communication at the University of Tirana in 2025, while the qualitative data were collected through 23 semi-structured interviews with journalists, editors, and editors-in-chief from both traditional and online media, as well as through a focus group of 14 participants from the same categories. The findings demonstrate that AI continues to be used at limited and mostly individual levels, while a tension exists between resistance and adaptation to its tools. Consequently, professional boundaries in Albanian journalism are being reshaped under the influence of AI, raising broader implications for professional education and the preparation of future journalists.